A study investigate the impact of lead pellet to the air pistol and air rifle shooters health in Subang National Shooting Range - Azuha, Mat Ail (2013)
Handling of lead pellets among the Air Pistol and Air Rifle shooters are the potential risk that may have adverse effect on the shooter’s health. In shooting course of action, shooters need to physically handle lead pellet, susceptible to inhaling the lead dust or fume and the improper ventilation system may increase the lead contaimination in the shooting range. Limited of empirical evidence focusing on the lead pellet effect to the shooters has created some difficulty to the researcher to complete the research. The reseach was conducted among the Air Pistol and Air Rifle shooter in the Subang National Shooting Range with the objective to the determine the contributing factors i.e physical contact, inhalation and ventilation system that may have impact to the shooter health status